1988
DOI: 10.1063/1.454388
|View full text |Cite
|
Sign up to set email alerts
|

State-to-state N2(A 3∑+u) energy pooling reactions. II. The formation and quenching of N2(B 3Πg, v′=1–12)

Abstract: We have studied the state-to-state excitation of N2(B 3Πg, v′=1–11) in energy pooling reactions between N2(A 3∑+u, v′=0,1) molecules and subsequent quenching in collisions with molecular nitrogen. Excitation of vibrational levels 10, 2, and 3 appears to be much stronger than excitation of the other vibrational levels. In addition, we failed to observe any emission from v′=12 even though it is energetically accessible. The excitation rate coefficients are quite large, 7.7×10−11 cm3 molecule−1 s−1 for the poolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(79 citation statements)
references
References 41 publications
2
76
0
1
Order By: Relevance
“…which rate coefficients (see Table 4) are given by Piper [1988a] and Piper [1988b] for processes (18) and (19), respectively.…”
Section: Gordillo-vazquez: Vibrational Kinetics A00e25 A00e25mentioning
confidence: 99%
“…which rate coefficients (see Table 4) are given by Piper [1988a] and Piper [1988b] for processes (18) and (19), respectively.…”
Section: Gordillo-vazquez: Vibrational Kinetics A00e25 A00e25mentioning
confidence: 99%
“…It is also shown that at such low N 2 partial pressures the N 2 1pbs emissions intensity is stronger than at higher N 2 partial pressures (e.g., 0.210 Torr). This was attributed [26] to the lower Ar efficiency in quenching N 2 (B 3 P g ) compared to that of N 2 . This means that there are excited N 2 emissions observable even at lower N 2 (partial) pressures than those in [16].…”
Section: The Role Of Oxygenmentioning
confidence: 87%
“…The constants k 1 À k 5 were determined [26,27,30,[38][39][40][41]. In any event calculations show that even though there maybe a very large difference in concentration between N 2 (B 3 P g ) and O 2 ðb 1 R þ g Þ or 2O 2 (a 1 D g ), primarily the very large difference in lifetimes between them and secondarily the quenching (by O, N, NO, even O 3 , etc.)…”
Section: The Role Of Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation decay of N 2 (B,v=11) (transition B,v=11 -A,v=7, λ = 580.4 nm) is low before quenching, thus the decrease is mainly due to [19]:…”
Section: Determination Of the Absolute Concentration Of An Excited Spmentioning
confidence: 98%